Design and practical evaluation of a shielded application system for intravenously administered radionuclide therapies - Kühnel, Christian; Winkens, Thomas; Niksch, Tobias; Greiser, Julia; Schrott, Steffen; Drescher, Robert; Freesmeyer, Martin (Nuklearmedizin - NuclearMedicine, 2020)
Aim Intravenous radionuclide therapies are gaining importance. With the increased frequency of these therapies, safe application procedures in combination with effective radiation protection are needed. We present a shielded system which can be universally used for the application of liquid radiopharmaceuticals.Materials and methods The application system consists of a cuboidal box made of lead with stainless steel coating, an inner layer of polymethyl methacrylate (PMMA), a disposable line/bottle system, and a medical infusion pump. No proprietary disposable parts are used. The system was tested and validated ex-vivo, and evaluated for Lu-177 peptide receptor radionuclide and for radioligand therapies (PRRT, RLT).Results Construction of the application system was performed in accordance with the physical characteristics of the used isotopes. 10 validation procedures with 1 GBq Tc-99m-pertechnetate confirmed functionality. 38 PRRT and 13 RLT procedures were performed successfully and completely. At least 98 % of the prescribed activities were infused. No leakage of radioactivity occurred. Dose rate measurements showed that the radiation in the box is shielded completely, and that exposure arises only from the infusion line outside the box and from the patient.Conclusion The presented application system for intravenous radionuclide therapies is feasible, safe, and cost-efficient. It has been shown that Lu-177-PRRT and -RLT can be performed without complications while ensuring nearly complete infusion of the prescribed radiopharmaceutical dose. Radiation exposure of the applying physician and other staff is low. The construction of the shielding box ensures complete shielding of all radionuclides currently used for radiomolecular therapies.
Keywords: radionuclide therapies; shielded application system; PRRT; RLT; infusion pump